Notes on law and police occupational culture in Brazil’s Military Polices: An explorative study - Julia Maia Goldani (Oñati International Institute for the Sociology of Law, 2021)
This research discusses the relations between law and police culture in the context of Brazil’s Military Polices, aiming to contribute both to discussions about these corporations’ non-compliance with legal standards and to socio-legal knowledge on policing. Pierre Bourdieu’s conceptualization of the juridical field, along with Erving Goffman’s theory of interaction rituals, are used to design a qualitative exploratory study that combines semi-structured interviews with lower-rank officers and observation of criminal trials in which these participated as witnesses. Due to COVID-19, methods were adapted to online platforms. The analysis suggests that Brazil’s juridical field structurally conditions the development of its police culture, although not in the ways intended. Additionally, law appears as an important symbolic figure in the construction of the officers’ occupational selves, and it is argued that contact with legal institutions engenders particular strategies of self-presentation, aimed at safeguarding both appearances and internal ideas about the profession.